2006
DOI: 10.1051/0004-6361:20065054
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive asteroseismic modelling of the high-amplitude δ Scuti star RV Arietis

Abstract: We present a comprehensive asteroseismic study of the double-mode high-amplitude δ Scuti star HD 187642 (RV Ari). The modelling includes some of the most recent techniques: 1) effects of rotation on both equilibrium models and adiabatic oscillation spectrum, 2) non-adiabatic study of radial and non-radial modes, 3) relationship between the fundamental radial mode and the first overtone in the framework of Petersen diagrams. The analysis reveals that two of the observed frequencies are very probably identified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
4
26
0
Order By: Relevance
“…A main result is that models with α ML = 1.5 did not produce any phase-shift versus amplitude-ratio diagrams compatible with the observations. This inefficiency in the convection for δ Sct stars was previously pointed out by Daszyńska-Daszkiewicz et al (2005); Casas et al (2006Casas et al ( , 2009. Other parameters, like metallicity, were also taken into account, but the results on the mode identification did not change.…”
Section: Mode Identification From Strömgren Photometrymentioning
confidence: 59%
“…A main result is that models with α ML = 1.5 did not produce any phase-shift versus amplitude-ratio diagrams compatible with the observations. This inefficiency in the convection for δ Sct stars was previously pointed out by Daszyńska-Daszkiewicz et al (2005); Casas et al (2006Casas et al ( , 2009. Other parameters, like metallicity, were also taken into account, but the results on the mode identification did not change.…”
Section: Mode Identification From Strömgren Photometrymentioning
confidence: 59%
“…In particular, the authors found that loci in the amplitude ratio-phase difference diagrams (Garrido 2000) become both aspect and m-dependent. In Casas et al (2006), it was found that mode contamination is significant for radial modes in δ Scuti stars. Therefore, mode contamination should be then taken into account for the correct identification using amplitude ratio-phase difference diagnostic diagrams.…”
Section: Mode Contaminationmentioning
confidence: 99%
“…Using these tools, we performed a massive numerical study of HR 8799 in an attempt to constrain physical and theoretical parameters. In this work, we will follow the same scheme as that used for the study of RV Arietis, 29 Cygnis and 9 Aurigae (Casas et al 2006, 2009; Moya et al 2006).…”
Section: Introductionmentioning
confidence: 99%